2008
DOI: 10.2134/jeq2007.0317
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of Sulfate in Acidified Pig Slurry during Storage and Following Application to Cropped Soil

Abstract: Acidification of slurry with sulfuric acid is a recent agricultural practice that may serve a double purpose: reducing ammonia emission and ensuring crop sulfur sufficiency. We investigated S transformations in untreated and acidified pig slurry stored for up to 11 mo at 2, 10, or 20 degrees C. Furthermore, the fertilizer efficiency of sulfuric acid in acidified slurry was investigated in a pot experiment with spring barley. The sulfate content from acidification with sulfuric acid was relatively stable and ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
42
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 40 publications
7
42
1
1
Order By: Relevance
“…However, the absolute levels were low compared with previous investigations regarding total S content (Eriksen et al, 1995) and S emissions (Eriksen et al, 2008). An initial level of total S of 200 mg S g -1 may therefore indicate that the dietary ingredients, as well as the diets, did not contain excessive levels of S.…”
Section: Sulfur Turnovercontrasting
confidence: 78%
See 1 more Smart Citation
“…However, the absolute levels were low compared with previous investigations regarding total S content (Eriksen et al, 1995) and S emissions (Eriksen et al, 2008). An initial level of total S of 200 mg S g -1 may therefore indicate that the dietary ingredients, as well as the diets, did not contain excessive levels of S.…”
Section: Sulfur Turnovercontrasting
confidence: 78%
“…It has been found that acidification of slurry to pH 5.5 inhibits sulfate reduction (Eriksen et al, 2008Ottosen et al, 2009). Contrary to these observations, the dietary acidification in this experiment of 0.4 to 0.6 pH units did not appear to influence sulfate reduction (Fig.…”
Section: Sulfur Turnovermentioning
confidence: 99%
“…This treatment is currently performed at the farm scale in Denmark by addition of concentrated sulfuric acid (H 2 SO 4 ). The use of this additive is mainly governed by economic reasons since H 2 SO 4 is one of the cheaper acids available (Eriksen et al, 2008). In Denmark this practice has notably increased in recent years (Birkmose and Vestergaard, 2013) as the Danish legislation recommends this treatment to reduce NH 3 emissions (Hoeve et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Application of animal slurry to agricultural land is practiced worldwide to fertilize the soil and increase the organic matter content (11). At the same time, animal slurry is also a well-documented source of different pathogens such as Cryptosporidium spp.…”
mentioning
confidence: 99%
“…that may be released into the environment. Conventional slurry management leads to nutrient losses both during storage and when applied to the fields (11,40), and the slurry has an obnoxious smell. By separating the slurry mechanically as well as chemically into a solid fraction that is typically composted before use and a liquid fraction used to fertilize the paddocks, nutrient losses and smell problems are reduced (12).…”
mentioning
confidence: 99%